Design and Fabrication of Delta Robot with Voice control - Bala Maga Ganapathi G.S. (IAES International Journal of Robotics and Automation (IJRA), 2015)
The objective of the project is to design and control the Delta robot with voice for pick and place operation using ARM7 processor. Till now there is no implementation of voice recognition and control in Delta robot. The maximum payload of the robot is 200grams-300grams. The robot has been made based on the SEQUENTIAL QUADRATIC PROGRAMMING. Various links of the robot are controlled using the servo motor and the gripper is separately controlled by a servo motor.